2014
DOI: 10.1089/fpd.2013.1615
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, PFGE Typing, and Antibiotic Resistance ofBacillus cereusGroup Isolated from Food in Morocco

Abstract: This article reports the prevalence and antibiotic resistance of the Bacillus cereus group isolated from different foods (milk and dairy products, spices, and rice salad) in Morocco. In total, 402 different food samples collected from 2008 to 2010 were analyzed by microbiological methods to isolate B. cereus. The strains were subjected to a polymerase chain reaction test in order to verify whether they belonged to the B. cereus group. Sixty-four of all isolates (15.9%) were found to be positive. Among the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 14 publications
5
22
7
1
Order By: Relevance
“…A comparison of the prevalence of B. cereus in raw milk from international studies is shown in Table 1. The prevalence of B. cereus in our study is higher than that Christiansson et al 1999) in Canada (8.5%) (Lina et al 1998), Czechoslovakia (15.5%) (Banyko and Vyletelova 2009) and Finland (20.8%) (Ruusunen et al 2013), but lower than that in Sweden (41.5%) (Svensson et al 2004), Morocco (47.8%) (Merzougui et al 2014). Another recent study from Wisconsin confirmed the presence of B. cereus in 9%, 35%, 14% and 48% of raw milk, pasteurised milk, Cheddar cheese and ice cream samples, respectively (Tewari and Abdullah 2015).…”
Section: Resultscontrasting
confidence: 72%
See 3 more Smart Citations
“…A comparison of the prevalence of B. cereus in raw milk from international studies is shown in Table 1. The prevalence of B. cereus in our study is higher than that Christiansson et al 1999) in Canada (8.5%) (Lina et al 1998), Czechoslovakia (15.5%) (Banyko and Vyletelova 2009) and Finland (20.8%) (Ruusunen et al 2013), but lower than that in Sweden (41.5%) (Svensson et al 2004), Morocco (47.8%) (Merzougui et al 2014). Another recent study from Wisconsin confirmed the presence of B. cereus in 9%, 35%, 14% and 48% of raw milk, pasteurised milk, Cheddar cheese and ice cream samples, respectively (Tewari and Abdullah 2015).…”
Section: Resultscontrasting
confidence: 72%
“…), Morocco (47.8%) (Merzougui et al . ). Another recent study from Wisconsin confirmed the presence of B. cereus in 9%, 35%, 14% and 48% of raw milk, pasteurised milk, Cheddar cheese and ice cream samples, respectively (Tewari and Abdullah ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Rather, Aulakh, Gill, Verma, and Rao (), detected B. cereus presence of 33,33% in raw milk and 37.83% in pasteurized milk samples. Merzougui, Lkhider, Grosset, Gautier, and Cohen () reported of B. cereus contamination of 51.6% in milk and dairy products. Cosentino, Mulargia, Pisano, Tuveri, and Palmas () reported the existence of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%